(untitled) (Journal of the College of Basic Education, 2023)
In the present work, have measured the radon gas concentration in ten cement samples from different countries like, (Iraq,Egypt,Iran,Lebanon,Turkyi and Jordan) by using alpha-emitters registrations which are emitted from radon gas in (CR-39) nuclear track detector. The obtained results have shown that the Maximum average value of radon gas concentration in cement samples which was (37.68 Bq/m3) origin of Turkish, while the lowest average of radon gas concentration in cement samples Delete which was (17.87 Bq/m3) origin of Iraq (Najif).The present results Show the radon gas concentration in all cements samples was below the allowed limit from (International Commission of Radiation Protection) (ICRP) agency.